John Steinbeck at the Hotel Madrid in Spain (Spain; Sevilla, 2022)
John Steinbeck sits with friends, Swedish artist Bo Beskow, (his hand to his mouth) and Jan and Chan Cainfarra on the patio at the Hotel Madrid in Spain. See photo 0-824. Original in safe.